Robust Controller Design for Two Wheeled Inverted Pendulum System - Ali, Hazem I.; Shareef, Zain AlAbdeen M. (Al-Nahrain Journal for Engineering Sciences, 2017)
In this paper, the design of a robust controller for two wheeled inverted pendulum (TWIP) system is presented. In the first stage of the design, a full state feedback H2 control is designed for stabilizing the inclination of (TWIP) system to upright position. The H? controller for the stabilized system is synthesized in the second stage. The mathematical model of the system based on the Newtonian approach is developed. The results verify that the proposed controller can compensate the system parameter uncertainty with a more desirable time response specifications.